Reaksi Pasar Atas Informasi Corporate Social Responsibility - mutira, putri mutira (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
Purpose – The purpose of this paper is to identify the effects of  Corporate Social Responsibility (CSR) disclosure on market reaction with Earning Response Coefficient (ERC) as proxy. Data/Object/Metodology – The researcher used secondary data obtained from Indonesian Stock Exchange. The level of the information of Corporate Social Responsibility measures by environment and social indicator in Global Reporting Initiative (GRI) 2006. Data were analyzed using  regression analysis Findings – The results showed that the CSR disclosure proven negative effect on Earnings Response Coefficient (ERC). This result indicates CSR information disclosed is not adequate for investor to consider its information for their investment decision.